Aspek Psikiatrik pada Pasien Luka Bakar dan Penatalaksanannya - Surilena Surilena (Fakultas Kedokteran Universitas Kristen Krida Wacana, 2004)
Throughout history as well as in literature, the devastating effects of fire burn on man and property have created both fear and respect for this element. Major burn in one of most severe trauma a person can experience, with devasting effects on the skin, the largest organ in the body. Burn injury is one of the leading causes of trauma death and one of thirty leading causes worldwide of loss of life years due to premature mortality and years with disability. The impact of burn injury on pantients not only occurred on physical aspect, but also on psychiatric aspect that link back to the traumatic stress and permanent damage that occur to their body either in terms of their body function or cosmetically. Psychiatric problems that are often suffered after the physical injury can be mood disorder and anxiety disorder (Post traumatic syndrome disorders, simple phobia, social phobia and Somatoform disorder). As a clinician seeing the scars of burn patients are sometimes struck by the fact that some individuals with severe objective handicaps manage their lives well, while others with only minor residual damage experience a dramatic impact on their life situatian